Biosensor based on direct interaction between sample and light within a waveguide - Tso, Pui Ken. (2010)
Biosensor is an analytical device that detects and measures small changes of concentration in biological fluids, in which the information can be obtained by using spectrophotometric analysis. Traditional clinical biosensors are bulky and usually takes up to a few hours to days before analysis can be completed. This had spurred a demand to develop a more portable and faster biosensor which is capable of producing analytical result in a shorter period of time.